AQUEOUS PHASE REFORMING OF SORBITOL VIA GROUP II DOPED NI/AL2O3 CATALYST FOR VALUE ADDED CHEMICALS PRODUCTION - RAMLI, MUHAMAD FAIZ (IRC, 2017)
The rise of the energy demands has caused concern regarding the decrement of fossil fuel reserves and the pollution caused. New researches and many alternative ways in solving this depleting feedstock of natural gas were done. Besides, many eco-friendly and environmental friendly way of producing energy was also being developed widely as to preserve the nature from collapsing. Thus, a sustainable and eco-friendly way of hydrogen production is needed to feed the industry. Biomass has the potential to provide sustainable source of energy and organic carbon for the industry. The utilization of the oxygenated hydrocarbon from biomass sources lead to the findings of the behavior of polyol (sorbitol) from hemicelluloses in aqueous phase reforming over supported Nickel/Alumina (Ni/Al2O3) catalysts. The effects of metal loading on the Ni/Alumina support on the catalytic performance were also studied. The objectives of this project which are to synthesize and characterize Ni/Al2O3 catalyst promoted by a cheap promoter Magnesium (Mg) for aqueous phase reforming (APR) of sorbitol and to conduct APR of sorbitol as to identify the value-added chemical that will be produced. The catalyst will be first synthesized using the wet impregnation method then it will later be characterized by using several ways include Thermogravimetric Analysis (TGA) and Scanning Electron Microscopy (SEM),